Correlation Between Poor Defecation Habits and Postoperative Hemorrhoid Recurrence - Li, Qing; Ghoorun, Roshan Ara; Li, Li; Zhang, Heng; Zhang, Dan; Qian, Haihua; Ren, Dong-Lin; Su, Dan (Frontiers in Surgery, 2022)
Background: The relationship between hemorrhoid recurrence and poor defecation habits is poorly understood. We aimed to analyze the effects of poor defecation habits on postoperative hemorrhoid recurrence. Materials and method: We performed a retrospective study on 1162 consecutive patients who underwent a surgical procedure for hemorrhoids at the Sixth Affiliated Hospital of Sun Yat-Sen University from December 2016 to May 2020. All patients were followed for 12 months post-operatively. Patients were monitored for disease recurrence and treatment satisfaction. Patient defecation habits were assessed using an obstructive defecation syndrome (ODS) score. Results: Patients with a score of 0–4 had a mild defecation disorder, 5–8 a moderate defecation disorder, and 9 or more ODS. Of the 1162 patients, 1144 (98.45%) had a mild defecation disorder, 13 (1.12%) had a moderate defecation disorder, and 9 (0.43%) had ODS. Older patients were significantly more likely to have worse defecation habits (P < 0.001). A higher ODS score correlated with a higher maximum anal squeeze pressure (P = 0.07) and a more severe inability for the anus to relax during simulated evacuation (P = 0.002). The maximum rectum threshold was also found to be the highest in ODS patients (P = 0.010). The proportion of PPH was the highest in the moderate defecation disorder group (53.85), followed by the ODS group (40.00) and the mild defecation disorder group (P = 0.023). Recurrence occurred in 5.51% of patients in the mild defecation disorder group, 38.46% of the moderate defecation disorder group, and 60% of the ODS group (P < 0.001). Multivariate analysis confirmed a higher ODS score (P < 0.001) and hematochezia (P<0.001) were independent predictors of recurrence. Furthermore, patients who occasionally exercised (P = 0.01) and patients who exercised regularly (P = 0.021) were less likely to have a recurrence. Patients in the moderate defecation disorder group and the ODS group were less satisfied with their surgical procedure compared with patients in the mild defecation disorder group (P < 0.001). Conclusion: Patients with unresolved defecation disorders are more likely to have their hemorrhoids recur and are unlikely to be satisfied with surgical management.